TEACHER INTERACTION FROM THE PERSPECTIVE OF HIGH SCHOOL STUDENTS - Szabó, László Dávid (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Based on Leary’s interpersonal model (Interpersonal Circumplex), Wubbels elaborated the scheme of interpersonal behaviour that was completed by questionnaires (Questionnaire on Teacher Interaction (QTI)). Our research involved 110 high school students. The aim of our present research is to determine the teacher’s interaction style from the high school students’ perspective using the QTI measurement tool (Questionnaire on Teacher Interaction). The purpose of the research is to assess how students see the teacher’s classroom activities and how the teachers see themselves and see whether there is a difference between the teacher’s own point of views and the students’ point of view. The questionnaire contains 48 items. This measurement tool can serve as a valuable source of information for teachers in comparing their own self-evaluation with the student’s perspective, which can obviously help their professional development.